2015
DOI: 10.4103/1305-7456.172637
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of audiovisual distraction eyewear and computerized delivery of anesthesia during pulp therapy of primary molars in phobic child patients

Abstract: Objectives:The aim of this study is to assess the effectiveness of audiovisual distraction technique with video eyewear and computerized delivery system-intrasulcular (CDS-IS) during the application of local anesthetic in phobic pediatric patients undergoing pulp therapy of primary molars.Materials and Methods:This randomized, crossover clinical study includes 60 children, aged between 4 and 7-year-old (31 boys and 29 girls). Children were randomly distributed equally into two groups as A and B. This study inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 21 publications
5
37
1
3
Order By: Relevance
“…In contrast to our finding from the previous study[17] which demonstrated that the use of video eyewear may provide better distraction than watching video on a screen where occlusive eyewear projects, the images right in front of the eyes of the user, blocking out real world's visual and auditory stimuli; the present study demonstrated a significant increase in the heart rate for group who underwent pulp treatment while watching video using video eyewear. Furthermore, self-reported mean pain score increases during treatment sessions' with video eyewear for both groups.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our finding from the previous study[17] which demonstrated that the use of video eyewear may provide better distraction than watching video on a screen where occlusive eyewear projects, the images right in front of the eyes of the user, blocking out real world's visual and auditory stimuli; the present study demonstrated a significant increase in the heart rate for group who underwent pulp treatment while watching video using video eyewear. Furthermore, self-reported mean pain score increases during treatment sessions' with video eyewear for both groups.…”
Section: Discussioncontrasting
confidence: 99%
“…[17] An effective pain control is important to achieve comfort, cooperation, and compliance in children during dental treatment. [18] In our study, we used CDS (Wand, Milestone Scientific, Inc., Deerfield, IL, USA) enabling slow-paced delivery of local anesthetic in small volume under a controlled low pressure of 165 pound/square inch.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the present study Morris et al concluded that by diverting the attention from an unpleasant medical setting to a pleasant and absorbing virtual world, virtual reality can markedly diminish patient's subjective pain experience. [28] In the recent studies conducted by Asvanund et al, [29] Khotana et-al, [8] Fakhurdin et-al and Hoge et al, [1,6] the results are corresponding to the current study where a significant reduction in anxiety and positive behaviour was instilled via the videoeyeglass in pediatric dental patients. Moreover in the present study, sedated children with N2O/O2 showed reduction in anxiety as depicted by pulse rate and Venham's anxiety scores.…”
Section: Discussionsupporting
confidence: 72%
“…Numerous pharmacological and nonpharmacological techniques have been proposed for achieving non-disruptive behavior during the dental treatment. [6] Among the nonpharmacological methods distraction and among the pharmacological techniques conscious sedation with N2O/O2 seem very promising in managing anxious children during the dental treatment, but there is dearth in literature about the comparison between the two techniques. [7] Based on the theory of Mc-Caul and Mallot, a patient's pain perception is decreased when he is distracted from an unpleasant stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to our findings from a previous study which demonstrated that the use of video eyewear might provide better distraction than watching video projected on a conventional screen. [11] In this study, AV distraction also served as an effective behavior modification tool, resulting in a statistically significant decrease in anxiety and apprehension during dental procedures manifested by a significant decrease in pulse rates.…”
Section: Discussionmentioning
confidence: 92%